Renewable energy transition - MUSE, Abshir Yonis (KDI School, 2023)
This thesis investigates the influence of Official Development Assistance (ODA), public investment, and foreign direct investment (FDI) on Africa's transition to renewable energy. The study employs a natural logarithmic transformation and utilizes both simple linear regression and multiple panel ARDL models to examine the causal effects. The analysis reveals a positive and statistically significant association between ODA and the transition to renewable energy, with a 1% increase in ODA corresponding to a 0.07% increase in the share of renewable energy in total consumption. Control variables, such as GDP growth rates, also indicate a positive impact on the transition. The findings align with previous research on economic growth and electricity consumption. However, public investment and FDI do not show significant impacts on renewable energy consumption. Based on the results, policy recommendations are provided. It is crucial to address disparities in investment outcomes to maximize the effectiveness of ODA in facilitating the transition to renewable energy sources in Africa. Cross-regional policy targets should be prioritized. Additionally, the study highlights the need to reassess investments made by African economies in renewable energy sources, which have yielded insignificant effects so far.
Thesis(Master) -- KDI School: Master of Development Policy, 2023
Keywords: Energy policy--Africa; Renewable energy resources--Africa